Efficacy and safety of CD22-specific and CD19/CD22-bispecific CAR-T cell therapy in patients with hematologic malignancies: A systematic review and meta-analysis - Li, Lili; Wang, Luqin; Liu, Qinhua; Wu, Zhonghui; Zhang, Yulong; Xia, Ruixiang (Frontiers in Oncology, 2022)
Background CD22 single and CD19/CD22 bispecific targeted chimeric antigen receptor T (CAR-T) cell therapy are promising immunotherapy modalities for the treatment of hematologic malignancies. The aim of this study was to assess the efficacy and safety of CD22 and CD19/CD22 targeted CAR-T cell therapy by summarizing the existing evidence. Methods Electronic databases including PubMed, Embase, and Scopus were comprehensively searched from inception up to November 30, 2022. Pooled response rates and minimal residual disease (MRD) negative response rates, cytokine release syndrome (CRS) rates and neurotoxicity rates were calculated. Subgroup analysis was performed based on the type of immunotherapy. Results Ten clinical studies including 194 patients with hematologic malignancies were included after a systematical screening of literature. The pooled complete response (CR) rates of CD22 and CD19/CD22 CAR-T cell therapy for relapsed or refractory B-cell lymphoblastic leukemia (B-ALL) were 0.75 (95% CI: 0.60 - 0.88) and 0.87 (95% CI: 0.76 - 0.96). The overall MRD negative response rates of CD22 and CD19/CD22 CAR-T were 0.54 (95% CI: 0.42 - 0.66) and 0.91 (95% CI: 0.47 - 0.88). Pooled CRS rates of CD22 targeted and CD19/CD22 targeted immunotherapy were 0.92 (95% CI: 0.82 - 0.98) and 0.94 (95% CI: 0.82 - 1.00), respectively. Conclusion Both CD22 and CD19/CD22 CAR-T immunotherapy demonstrated favorable efficacy and acceptable adverse events in the treatment of hematologic malignancies. Well-designed and large sample-sized clinical trials are warranted.